Tingkat Stres Atlet Atletik PPLP Jawa Tengah Dimasa Pandemi Covid-19 - Viola Yashmak Candra Zenana; Said Junaidi; Heny Setyawati (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
The existence of the Covid-19 pandemic in Indonesia has an impact on athletic athletes, one of which is mental health such as stress. Those activities cause the decreasing intensity of the athlete's training and lead to the decreasing athlete's performance in the future. If these continue to happen without good stress management, the stress levels will increase. This study used a quantitative research approach, namely the positivism philosophy research method. It was used to examine certain populations or samples. The research instruments used to collect the data. This study employed a quantitative/statistical data analysis. The type of this research is survey research. Survey research was used to provide a clear boundary about the data to determine the stress level of Central Java PPLP athletic athletes during the Covid-19 pandemic. This study used descriptive statistical data analysis techniques with percentages. The results of this study showed that the level stress of PPLP Central Java athletic athletes during the Covid-19 pandemic was in the category of "very low" by 0% (0 people), "low" by 0% (0 people), "enough" by 29% (5 people), “high” by 71% (12 people), and “very high” by 0% (0 people). Based on the results, 75.67% stress level of PPLP Central Java athletes during the Covid-19 pandemic is high.